Clinical legal education as an effective way of training lawyers - Kravchuk, Mykola; Grytsan, Olha (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article examines the issue of the effectiveness of clinical education in the preparation of future specialists in the field of law. The main groups of practical skills that students who are attracted to work in legal clinics receive are highlighted and characterized. These include: legal problem solving skills, communication skills, counseling skills, negotiation and mediation skills, skills in drafting procedural documents, skills in solving ethical professional tasks. It is noted that the main advantage of clinical training of lawyers, compared to purely academic, is the acquisition of practical skills in parallel with the acquisition of theoretical knowledge. Clinical training courses can fill the gaps in the purely theoretical training of lawyers.The current state of teaching a special course of clinical education in Ukraine in legal institutions of higher education is analyzed. According to the authors, the role of clinical education for the training of future lawyers in Ukraine is underestimated. Conclusions are made about the need to strengthen the role of legal clinics through the widespread introduction of courses on legal clinical practice in the educational process. In order to increase the efficiency of legal clinical education, it is necessary to introduce it into the educational process as a mandatory element. The opinion is expressed that equipping students with practical skills should become a basic aspect of educational activities of legal institutions of higher education.